Development of an Effective Process of Saw Gining of Raw Cotton - Kakhramonovich Sаbirov Islom (European Journal of Life Safety and Stability (2660-9630), 2021)
The development of a highly efficient technology of saw gin to increase the unit capacity with an increase in plant productivity and product quality, reducing its cost, facilitating the maintenance and repair of gin.